FAM175B promotes apoptosis by inhibiting ATF4 ubiquitination in esophageal squamous cell carcinoma - Yu Zhao; Yang Yu; Hengcun Li; Zheng Zhang; Shuilong Guo; Shengtao Zhu; Qingdong Guo; Peng Li; Li Min; Shutian Zhang (Molecular Oncology)
FAM175B is a reported regulator of p53 and suppresses tumorigenesis in numerous types of cancer, but very little is known about its function in esophageal squamous cell carcinomas (ESCCs), almost 70% of which exhibit mutations in p53. Here, we report that FAM175B expression is downregulated in high‐grade intraepithelial neoplasia (t = 2.44, P = 0.031) and ESCC (t = 5.664, P < 0.001) tissues relative to that in adjacent normal esophageal tissues. Exogenous expression of FAM175B in ESCC cells resulted in a decrease in proliferation rate, inhibition of colony formation, and an increase in apoptosis rate. Knockdown of FAM175B produced the opposite results. Furthermore, confocal microscopy and coimmunoprecipitation assay showed that Activating transcription factor 4 (ATF4) colocalized and interacted with FAM175B. Ubiquitination assays revealed that FAM175B inhibited ubiquitin‐dependent ATF4 degradation and elevated ATF4 protein level. Finally, luciferase reporter experiments further clarified that FAM175B promoted CHOP expression in an ATF4‐dependent manner. Accordingly, the proapoptotic activity of FAM175B was significantly rescued by treatment with si‐ATF4 and the CHOP inhibitor 4‐PBA. In summary, FAM175B inhibited ATF4 ubiquitination and promoted ESCC cell apoptosis in a p53‐independent manner. FAM175B expression loss may be an early diagnostic biomarker in ESCC patients.